Entendendo expectativas e percepções sobre a qualidade dos serviços prestados por uma ESFL - Nascimento, Natália Figueira do (2018)
This paper is dedicated to understand the relationship between the supplier and the customer in the context of professional learning. The supplier is an entity that qualifies young learners, called Instituto Alfa, and the customer is the company that hire these young learners. The study is based on the understanding and structuring of the processes that involve the provision of services by the entity, which supports the adequacy of the SERVQUAL questionnaire, a research tool proposed by Parasuraman, Zeithaml and Berry (1985), that assesses expectations and perceptions from customers about the quality of the service delivered. The questionnaire was sent to 93 partners of Instituto Alfa in the city of Uberlândia, and after approximately 40 days, 22 responses were obtained. The evaluation of the expected and perceived quality was based on the evaluation of seven constructs: tangibility, reliability, responsiveness, safety, empathy, pedagogical aspects and psychosocial aspects. The dimensions that were most important in the evaluation of the partners were the psychosocial aspects and pedagogical aspects, and the latter was the one that presented the greatest gap (difference between expectations and perceptions).